Wear-resistant Coatings From Electroerosive Micro- and Nanofraction Powders - E.V. Ageeva; L.P. Kuznetsova; E.V. Ageev; A.Yu. Altukhov; O.V. Vinokurov; V.V. Sirota (Журнал нано- та електронної фізики)
The results of studies of relative stability of the cutting tool, restoration and strengthening by electric-spark alloying with the using as electrode material the electroerosive tungsten powders are demonstrated. The efficiency of their application is shown.